Determinación de la tasa de descuento para evaluar la rentabilidad de un emprendimiento local de secado de frutas y vegetales - Alpízar-Alpízar, Gabriela; Ugalde-León, Mónica; Vargas-Brenes, Adolfo (Instituto Tecnológico de Costa Rica, 2017)
This project is a consequence of a previous Pre - feasibility and Marketing strategy studies developed by the authors for several courses of the Master in Business Admistration´s program. It offers to the reader a guide for obtaining an appropriate discount rate according to its industry and country. This will be useful for discount the net cash flows and give more quality to the finance information for the investor of an entrepreneur business located in Costa Rica, to achieve better decisions. The main objective was to define an optimums discount rate, structured by theoretical and methodological frameworks to achieve a final model conformed by indicators that allows conclude and give advices to both, our readers and potential investors. The theoretical framework embraces elements related to three main columns: the dehydrated food techniques, the capital cost and the financial valuation of projects. The financial analysis of the entrepreneur project using indicators such as: payback period, net present value, annualized cost-benefit, among others. The methodological strategy allowed obtain a final sampling of five corporations with similar products to those of the enterprise, all of them located in the United States of America. Its financial statements were analyzed and a finally a weighted average cost of capital was obtained specifically for this project. It concludes that the present projects represents a guide for establishing the optimums discount rate for an entrepreneurship, even related with different industries, because it gives a general guide for de analyst.
Proyecto de Graduación (Maestría en Administración de Empresas con énfasis en Finanzas) Instituto Tecnológico de Costa Rica. Escuela de Administración de Empresas, 2017.
Keywords: CPPC; Estados financieros; Estudios financieros; Toma de decisiones; Sector agroindustrial